The influences of dietary protein on bovine placental development and ovarian function - Edwards, Jennifer L. (2017)
Dietary protein is a vital nutritional component in beef production due to its essential contribution to optimal reproductive efficiency, neonatal and post-pubertal growth rates. Cattle have had a declining fertility rate for several decades and previous literature has indicated a possible interaction with the high dietary protein levels. The two most critical structures influencing pregnancy are the ovary and placenta, therefore this study consisted of two experiments. Experiment 1 investigated the influence of changing dietary protein during the peri- and post-conception period on these structures. Experiment 2 investigated the effect of dietary protein in the non-pregnant beef heifer on a commercial farm setting. The hypothesis underpinning this study is that optimal dietary protein levels are required for maximal placental and ovarian function. To test this hypothesis two experiments were conducted. In experiment 1, Australian nulliparous Bos indicus: Bos taurus cross heifers were fed isocaloric high (14%) or low (7%) crude protein diets (individually) from -60 days post-conception (dpc) to 23 dpc. Between 23dpc and 98dpc two groups then were fed either high or low crude protein diet which established four treatment groups. Treatments were assessed after the first trimester (98dpc) in order to investigate acute effects and at term in order to determine effects at parturition. At 98dpc, 46 heifers were slaughtered and adult ovaries, placental tissue and fetal tissues were collected. The remaining 56 heifers were maintained on the same diet at recommended NRC recommended protein levels until calving. Immediately post-partum placentomes (3-5) were collected and characteristics of parturition (e.g. length, difficulty) recorded. Histological techniques were used to visualise the cellular composition of the placental structure and to determine the level of vascularisation within the placenta. Deep sequencing of the global gene expression of the placenta was determined using the Illumina platform and qRTPCR analysis. At 98dpc the high dietary protein level stimulated the relative volume densities of the maternal tissue, in a sex specific manner, but had no effect on the fetal trophoblast cells. The LPERI diet increased the placental collagen proportion, which was also observed in the relative volume densities of the maternally derived collagen within the placentomes supporting female offspring. The HPERI diet also altered the vasculature by increasing the proportion of tissue occupied by blood vessels. Transcriptomic analyses of gene expression in the placentome showed the HPERI diet affected genes associated with inflammation and wound responses in the placentomes supporting male offspring. In the term placenta, the high protein diet increased the perimeter and area of blood vessels, but decreased proportion of tissue occupied by blood vessels. High protein also induced differential expression of genes associated with inflammation, a process integral to successful parturition. In experiment 2, British nulliparous Angus cross heifers received control (10.4%) or high (14.5%) crude protein isocaloric diets for >60 days before slaughter, where ovaries and jugular blood were collected. Follicles were aspirated to remove follicular fluid (FF) and granulosa cells (GCs). Histological techniques were used to visualise the level of vascularisation in the corpus luteum (CL). Circulating serum metabolites and hormone levels were also determined by auto-analysis and ELISAs. Global gene expression of the ovarian granulosa cells (GCs) was determined using the Illumina platform and qRTPCR analysis. The high protein diet increased both the antral follicle count (AFC) and carcass quality, as measured by increased numbers of heifers falling into the higher grades. Analysis of serum and follicular fluid identified differences in urea, albumin, and non-esterified fatty acid levels induced by high dietary protein. Transcriptomic analysis of GC cells from control and high protein diets identified differential expression of genes associated with increased proliferation in the high protein group. In conclusion, these studies showed that dietary protein level affected both placental and ovarian function. Furthermore, the dietary treatments impacted on gene expression associated with feto-placental growth and parturition.